PHYSICOCHEMICAL CHARACTERISTICS OF BABY JAVA ORANGE PEEL PECTIN (Citrus sinensis) AND CORN STARCH-BASED EDIBLE FILM WITH GLYCEROL PLASTICIZER - Lilis Suryani Karlan; Safinta Nurindra Rahmadhia (Fakultas Teknologi Pertanian Universitas Brawijaya, 2022)
Baby Java orange is one sweet orange variant with a high pectin content on its skin. Pectin and starch are examples of the main ingredients in making edible films. Besides its economical price, corn starch is also commonly used in preparing edible films as the biopolymer material that can produce a matrix used for the edible film preparation process. The addition of glycerol plasticizers can improve the structure of the film. This study aimed to determine the effect of pectin concentration of Baby Java orange peel and glycerol on the physicochemical characteristics of the resulting edible film and determine the formulation with the highest value in the manufacture of the edible film according to the Japanese Industrial Standard (JIS). This study used a Completely Randomized Design (CRD) with two factors. The first factor is Baby Java skin pectin concentration (15%, 25%, and 35% %b b/b starch), while the second factor is glycerol concentration (10%, 20%, and 30% v/v). The edible films were then analyzed for their moisture content, thickness, solubility, color, tensile strength, and water vapor permeability. The results show that the concentration of pectin and glycerol with the addition of corn starch significantly affects the parameters of moisture content, solubility, thickness, tensile strength, color, and water vapor permeability tests. The optimum formulation in the preparation of edible films according to JIS was the formulation with the addition of 15% pectin and 20% glycerol, which resulted in 6.24% of moisture content, 76.57% solubility, 0.25 mm thickness, 0.50 MPa tensile strength, 54.98 lightness, 3.66 blueness, -1.48 appearances and 1.42 g.mm/m2.h.kPa water vapor permeability